(untitled) (New York, 2000)
The only hands-on reference of its kind, the Handbook of Environmental Engineering Calculations equips you with step-by-step calculation procedures covering virtually every aspect of environmental engineering. Designed to give you quick access to essential information, the updated Second Edition of this unique guide now presents the latest methods for solving a wide range of specific problems, together with worked-out examples that include numerical results for the calculations. Written by a team of environmental experts from both the private and public sectors, this easy-to-use reference provides you with complete calculations for water quality assessment and control…solid waste materials … and air pollution control. Filled with 200 helpful illustrations, the Second Edition features: Hundreds of detailed examples and calculations with fully illustrated steps; calculations covering every aspect of environmental engineering; both SI and U.S. customary units presented throughout; and new to this edition: new sections on fuel cells and air toxic risk assessment.
Keywords: Environmental engineering,Công nghệ môi trường; Sổ tay, hướng dẫn, v.v..